Khansaa's relationship with politics in her poetry - Al Khatib, Asmaa Ahmed Ali (Journal of Humanities & Social Sciences, 2017)
The poetry of Al-Khansa has a high status among researchers, as they have explained and analyzed it from different aspects, as it could be easily seen by the specialists in this area. This study tried to investigate this poetry and analyze it to explore the relationship of the poet with politics in featured in her poetry.The study included positions that can be described as political, which appeared in the poetry of the poet, and were in relation to wars and revolutions. Besides, the findings indicated the existence of a political role promoted by the poet in this poetry; as a desired result of this study.Some examples of these positions are:Warning of the war dangers before it occurs; Urging revenge and encouraging and praising whoever takes revenge; talking about the sovereignty of the people and its conditions; protecting in the war, propagating the news of the victory of the tribe in a particular war; and urging herself to fight and participate in wars.It is also noticeable in this study that this political role played by the poet in her poetry was related only to her people and any related wars. This role did not extend to a wider scope of the affairs of other tribes.
Keywords: women; relationship; politics; attitudes